Why the dominance of East Africans in distance running? A narrative review - Grivas Gerasimos V.; Onywera Vincent O.; Marco-Contreras Luis Alberto; Sutehall Shaun; Muniz-Pardos Borja (Translational Exercise Biomedicine)
Runners from East Africa including Kenya, Ethiopia and Uganda have dominated middle- and long-distance running events, for almost six decades. This narrative review examines and updates current understanding of the factors explaining the dominance of East Africans in distance running from a holistic perspective.